Perancangan Company Website Pada CV. Karya Indah - Hardiasyah; Ian Mukti Herlambang; Febri Yanti Adnan; Thoyyibah Tanjung (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
The development of information technology in human life today has a very large influence on its activities. Especially in relation to the marketing sector that occurs in the process of buying and selling transactions. CV. Karya Indah which is engaged in services. The existing promotion system is still very simple. Consumers who want to consult service services must come directly by wasting time and are less efficient. The research methodology that will be discussed in this study there are 2 methods, including observation (observation) and the RAD method. The results obtained by the website can be run smoothly and also responsively. Websites can be used by CV. Karya Indah as their store information system without any problems. The division of tasks in the website development process can increase work productivity. Successfully designed the CV Karya Indah website using Visual Code, taking advantage of the features and standards contained in.